1996
DOI: 10.3354/meps145143
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring and analyses of physical factors regulating variability in coastal Antarctic phytoplankton biomass, in situ productivity and taxonomic composition over subseasonal, seasonal and interannual time scales

Abstract: A 3 yr high-resolution temporal data base related to phytoplankton dynamics was collected during the austral spring/sumrner periods of 1991 to 1994 in shelf waters adjacent to Palmer Statlon, Antarctica. Here, the data base is used [ l ) to quantlfy the vanabillty in phytoplankton biomass, In sjtu productivity and taxonomic composition over subseasonal, seasonal and interannual time scales; (2) to elucidate environmental mechanisms controlling these temporal patterns; and (3) to ascertain which phytoplankton m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 34 publications
(41 reference statements)
5
106
2
1
Order By: Relevance
“…Changes in the microbial community are difficult to quantify against a high background of temporal and spatial variability, but evidence indicates that dinoflagellate (Hallegraeff, 2010;McLeod et al, 2012) and Emiliania huxleyi (Cubillos et al, 2007) distributions are migrating poleward. Similarly, increased precipitation and glacial melt from warmer temperatures reportedly favours dominance of cryptophytes over diatoms in Antarctic coastal waters (Moline and Prézelin, 1996;Moline et al, 2004). In addition, the timing, duration and magnitude of phytoplankton blooms is defined by the impact of temperature on the physical environment (e.g.…”
Section: Temperaturementioning
confidence: 99%
“…Changes in the microbial community are difficult to quantify against a high background of temporal and spatial variability, but evidence indicates that dinoflagellate (Hallegraeff, 2010;McLeod et al, 2012) and Emiliania huxleyi (Cubillos et al, 2007) distributions are migrating poleward. Similarly, increased precipitation and glacial melt from warmer temperatures reportedly favours dominance of cryptophytes over diatoms in Antarctic coastal waters (Moline and Prézelin, 1996;Moline et al, 2004). In addition, the timing, duration and magnitude of phytoplankton blooms is defined by the impact of temperature on the physical environment (e.g.…”
Section: Temperaturementioning
confidence: 99%
“…Primary production in the WAP area follows closely the distribution of phytoplankton biomass measured as chlorophyll a (chl-a) concentration, and published values show a wide range of spatial and temporal variability (Smith et al, 1996a(Smith et al, , 1998aMoline and Prezelin, 1996). Concentrations are greatest nearshore with an onshore/offshore gradient of decreasing biomass towards the continental slope that follows a gradient in bottom topography and physical and optical properties (Smith et al, 1996a(Smith et al, , 1998c.…”
Section: Introductionmentioning
confidence: 99%
“…Data averaged for nearshore stations (B & E) and presented as a function of time during the growing season from 1991/92 through 1998/99. Data for the 1991/92 through 1993/94 season are estimated using photosynthesis irradiance curves integrated to 60 m (Moline and Prezelin, 1996). Data from 1994/95 through 1999/00 estimated from simulated in situ observations (SIS), as described in the text, integrated to the depth representing 2% of surface irradiance.…”
Section: Spatial and Temporal Variability Based On Discrete Field Obsmentioning
confidence: 99%
“…In general, phytoplankton blooms around the AP are typically associated with the development of a shallow mixed layer (retaining phytoplankton within adequate light levels) and with iron availability (e.g., Prézelin et al, 2000), and are reported to be typically dominated by diatoms and/or haptophytes (primarily P. antarctica). Nevertheless, several studies have highlighted the increasing importance of cryptophytes in the AP as they prevail over diatoms, particularly within ice melting regions (Moline and Prézelin, 1996;Moline et al, 2004). Several other studies have related the seasonal succession of phytoplankton along the west of the AP (wAP) to the timing of the sea ice retreat, particularly from the south of Gerlache Strait to Marguerite Bay (Garibotti et al, 2005;Prézelin et al, 2000), with some evidence found within the BS (Mendes et al, 2013;Varela et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, diatom blooms attain higher biomass when the sea ice retreat is under way and, with a continued stratification, cryptophytes can numerically replace these diatoms (Ducklow et al, 2007). Finally, a phytoplankton community co-dominated primarily by very small diatoms and other unidentified flagellates are associated with low Chl-a (Garibotti et al, 2005;Moline and Prézelin, 1996). There are numerous sources in the literature on phytoplankton dynamics in some wAP systems, principally near Marguerite Bay (Prézelin et al, 2004 and references therein).…”
Section: Introductionmentioning
confidence: 99%